Perancangan Sistem Manajemen Pergudangan di Laris Elektronik Solo - Patrick Eving; Herry Christian Palit (Jurnal Titra, 2020)
Laris Elektronik is a distributor of electronic house appliances whose sales targets are smaller stores. The current warehouse system which laris currently use is mainly done manually by human resources and is centered on the owner. A good system must never rely on a single individual and should be done in a regular order. The main purpose of this thesis is to create a better warehouse system which is more automatic and less dependant on the owner. There are 3 main improvements in this thesis, i.e. inventory control system, construction of a database for stocking purpose, and warehouse layout improvement.Inventory control system is done by changing the method of goods ordering into periodic review with 3 days duration. The duration is prolonged from the current 1 day review system because there are too many stock inspections done with the old system. The construction of database is done to hasten the input of stock datas and to give employees access toward a certain information regarding goods (e.g. Number of goods left, price of goods) that was originally known only by the owner. The layout improvement is done based on the preceding inventory control improvement. The current random goods layout is given order based on the speed of sales and optimal stock value which is decided in the inventory control system.